2016
DOI: 10.1002/ecs2.1345
|View full text |Cite
|
Sign up to set email alerts
|

A behavior‐based framework for assessing barrier effects to wildlife from vehicle traffic volume

Abstract: Roads, while central to the function of human society, create barriers to animal movement through collisions and habitat fragmentation. Barriers to animal movement affect the evolution and trajectory of populations. Investigators have attempted to use traffic volume, the number of vehicles passing a point on a road segment, to predict effects to wildlife populations approximately linearly and along taxonomic lines; however, taxonomic groupings cannot provide sound predictions because closely related species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 49 publications
9
113
0
2
Order By: Relevance
“…Moreover, Jacobson et al (2016) proposed a species susceptibility to road barrier effects to be related to their ability to recognize and respond to potential predators and threats. "Nonresponders" failed to recognize the threat and crossed irrespective of traffic conditions; "Pausers" stopped in the face of danger; "Speeders" fled in the face of danger; while "Avoiders" were able to recognize traffic as potential predators and began to avoid roads at lower traffic volumes.…”
Section: Habitat Augmentationmentioning
confidence: 99%
“…Moreover, Jacobson et al (2016) proposed a species susceptibility to road barrier effects to be related to their ability to recognize and respond to potential predators and threats. "Nonresponders" failed to recognize the threat and crossed irrespective of traffic conditions; "Pausers" stopped in the face of danger; "Speeders" fled in the face of danger; while "Avoiders" were able to recognize traffic as potential predators and began to avoid roads at lower traffic volumes.…”
Section: Habitat Augmentationmentioning
confidence: 99%
“…High traffic volume may deter observers from being able to make observations in these areas, where driving may take more vigilance or parts of the road and shoulder are more likely to be obstructed from view by other vehicles (Collinson ). Additionally, some species may be deterred from attempting to cross roadways that have high traffic flow and vehicle speed (Jacobson et al ). Overall, we found that the effect of traffic was the least important variable in predicting roadkill presence.…”
Section: Discussionmentioning
confidence: 99%
“…This follows both a similar diurnal pattern to road accidents with most collisions occurring during dusk and dawn, and a similar seasonal pattern with most accidents reported during autumn and winter (Neumann et al 2012;Borda-de-Água et al 2014;Rolandsen 2015). Likewise, as on roads (Seiler and Helldin 2006;Jacobson et al 2016), WTCs were more frequent on railways with intermediate traffic volumes (50-150 trains per day) and less frequent on both calmer and busier tracks.…”
Section: Collision Statisticsmentioning
confidence: 99%